Optimasi Formula Patch Transdermal Ekstrak Etanol Daun Seledri untuk Pengobatan Hipertensi - Ni Kadek Ayu Pramesti; I Putu Mas Arie Pradina Putri; Ni Putu Mas Arya Shinta; I Gusti Ngurah Jemmy Anton Prasetia (Berkala Ilmiah Mahasiswa Farmasi Indonesia, 2021)
Introduction: Hypertension is one of the biggest health problems for Indonesian people. Celery leaves are a plant that can be used to treat hypertension. Research shows that the ethanol extract of celery leaves at a dose of 150 mg / day can reduce blood pressure. Antihypertensive drugs have low oral bioavailability due to first pass metabolism in the liver. The use of transdermal patches can improve patient comfort and may improve low oral bioavailability. One of the important components in the patch preparation is a polymer matrix consisting of hydrophilic (PVP K-30) and hydrophobic (EC N-20) polymers. Methods: this review article using literature review and evaluation results from research journals. Results: Optimization of the formula for transdermal patch preparations was carried out using three variations of the ratio of PVP K-30 and EC N-20 for the transdermal patch polymer matrix, namely 1: 2, 2: 3, and 1: 3. The best transdermal patch formula of celery leaf ethanol extract in terms of physical characteristics parameters and has the potential to provide optimal release of active ingredients to reduce blood pressure, namely the formula with a combination of polymer matrix PVP K-30 and EC N-20 2: 3. Conclusion: The writing of this review article is to obtain the best comparison of hydrophilic polymer (PVP K-30) and hydrophobic polymer (EC N-20) in celery leaf extract patch preparations (Apium graveolens) which have the potential to provide optimal release of active ingredients to lower blood pressure.